Correlations between micro mechanical analyses and macro-scale mechanical properties of PPS/basalt fiber composites designed from commingled yarns - I. Castro-Cabrera; B. Gaumond; D. Cieslak; J.F. Gerard; S. Livi; J. Rumeau-Duchet (Polymer Testing)
To reduce the environmental impacts of the transportation while enhancing safety and fuel efficiency, the development of lightweight, high-performance composites is imperative. To meet this challenge, polyphenylene sulfide (PPS) composites reinforced with basalt fibers (BF) are investigated with a focus on advanced manufacturing techniques via commingled yarns (CY). In fact, basalt fiber-reinforced polymer composites (FRPCs) are promising candidates across diverse industrial -from automotive to aerospace-owing to their superior mechanical properties and thermal stability. This work bridges the gap between the micro and the macro-mechanical performance of PPS/basalt fiber yarns and their composites by systematically evaluating the key role of fiber-matrix interface. Two different sizing formulations were compared against unsized fiber -one based on polyamide-polyurethane and epoxy-unsaturated polyester. Comprehensive surface characterization including chemical composition analysis, micro-tensile testing, wettability, and morphology assessments, was performed to evaluate micro-scale performance. Pull-out adhesion test quantified improvements in the interfacial shear strength (IFSS) from up to 360 % relative to unsized fibers. At the macro-scale, interlaminar shear strength (ILSS) tests established a quantitative relationship with micro-scale phenomena, revealing a 60 % enhancement in mechanical performance when using the optimal film former. Lastly Weibull statistical analyses were performed to examine the role of sizing during CY processing on fiber failure distribution, demonstrating the effective protection provided to fibers during processing and distinguishing major differences between sizing formulation. Collectively, these results provide valuable insights for the design of high-performance composites based on basalt fibers and a PPS matrix.